A76 SINGLE OPERATOR PANCREATOSCOPY IN THE EVALUATION OF PANCREATIC NEOPLASMS: A CASE SERIES. (1st March 2018) - Hansen, T; Moffatt, D C
Abstract: Background: Pancreatic neoplasms are most commonly diagnosed by endoscopic ultrasound (EUS), computed tomography (CT) scan and magnetic resonance cholangiopancreatography (MRCP). However, all these imaging modalities have limitations in their ability to diagnose small main duct intraductal papillary mucinous neoplasm (MD-IPMN) or early pancreatic neoplasms. Single operator pancreatoscopy (SOP) is a new modality to diagnose pancreatic neoplasia that is gaining popularity as case series and a retrospective single-center study have been published showing favorable efficacy. Aims: This case-series was performed to evaluate our centre's experience with SOP. Methods: Patients who underwent SOP using the SpyGlass Direct Visualization System (Boston Scientific, Natick, Mass) between June 2013 and July 2016 were identified. Main outcome measurements included efficacy and safety of pancreatoscopy. Results: During the study period, 32 patients underwent SOP for evaluation of suspected IPMN or pancreatic duct neoplasia. Prior to SOP, all patients had either an EUS or MRCP. Twenty-two (68.8%) patients had an EUS while 29 (90.6%) had MRCPs with indeterminate features for MD-IPMN or pancreatic neoplasia. Twenty-one (65.6%) patients were female and the mean age was 64.9 ± 12.2 years at the time of procedure. Technical failure occurred in 6 (18.8%) patients. Samplings through biopsy or brushing, were performed in 8 (30.7%) of patients. Overall, 13 (40.6%) patients had a pancreatic duct neoplasia, MD-IPMN, side branch IPMN or combined IPMN. In one patient, the pancreatoscope could not be introduced into the pancreatic duct. High-risk patients (n=8) were considered to be individuals who were diagnosed with MD-IPMN with or without side branch involvement. One patient is currently awaiting surgery. Five patients (71.4%) were diagnosed with adenocarcinoma and 1 (14.2%) was diagnosed with a dysplastic cyst via surgical specimens. The last patient did not undergo surgery and is being followed with serial imaging that has yet to suggest malignancy. Of the 19 patients with a negative pancreatoscopy for IPMN, 0 have developed an IPMN or pancreatic neoplasm in mean follow up of 1.5 years (SD 0.67). In our series, if pancreatic duct cannulation is successful, SOP has a diagnostic accuracy, sensitivity and specificity of 92.3%, 100% and 90.4% respectively for determining high risk IPMN/pancreatic cancers at time of ERCP. Complications occurred in 2 (7.6%) patients, 1 (3.8%) mild post-ERCP pancreatitis and 1 (3.8%) contained perforation related to sphincterotomy. Prophylactic pancreatic stents were placed in 27 (84.4%) patients and rectal indomethacin was used in 27 (84.4%) patients. Conclusions: Our case-series suggests that SOP to evaluate for pancreatic neoplasia is safe and adds important information in the evaluation of pancreatic duct neoplasm that are not definitively diagnosed by EUS or MRCP. Funding Agencies: None